OCCUPATIONAL HEALTH AND SAFETY CONCERN IN COTTON INDUSTRY IN FAISALABAD - Hamid Mahmood; Khalid Ismail; Amjad Iqbal Burq et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT:Occupational health is the study of effect of work and the working environment on the health of the worker. Occupational diseases are those diseases, which arise out of or during working at employment place.